The Relationship Between Postnatal Care Service Quality and Patient Satisfaction After Birth - Amelinda, Amanda; Amalia; Lestari, Yuli (Global Indonesia Health Care (GOICARE), 2025)
Background: Quality of health care is the patient's needs as an indicator of service that shows patient satisfaction with the level of patient visits, and the way achieved the best quality through improving the quality of health services by increasing patient satisfaction. Purpose: The aim is to analyze the relationship between service quality and postpartum patient satisfaction in the Delima Room of RDUD Dr. H. Abdul Moeloek. Methods: Employing a cross-sectional design, 62 postpartum mothers were surveyed between January 23 and February 20, 2025, using purposive sampling. A structured and validated questionnaire was administered, measuring perceptions of service quality and satisfaction. Chi-square analysis was conducted using SPSS v25, with a significance threshold of p < 0.05. Results: The characteristics of the majority of respondents aged 20-29 years (58.1%), S1 education (35.5%), and IRT (50.0%). the relationship between the quality of postnatal care services with postpartum patient satisfaction obtained a significant value of p-value 0.000 (p <0.05), which means there is a relationship. There is a relationship between the quality of postnatal care services and postpartum patient satisfaction. Conclusion: RSUD can maintain the level of satisfaction of nursing services to patients and improve the quality of service optimally in order to achieve health service satisfaction, and can maintain and improve services that are considered good by patients, and improve services that still make patients feel less satisfied.